The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5054/tq.2011.268062
|View full text |Cite
|
Sign up to set email alerts
|

Narrow Viewing: The Vocabulary in Related Television Programs

Abstract: In this study, the scripts of 288 television episodes were analyzed to determine the extent to which vocabulary reoccurs in related and unrelated television programs, and the potential for incidental vocabulary learning through watching one season (approximately 24 episodes) of television programs. The scripts consisted of 1,330,268 running words and had a total running time of 203 hours and 49 minutes with a mean running time of 42 minutes. The vocabulary from a single season of six individual television prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 45 publications
4
105
0
2
Order By: Relevance
“…It would also be useful to look at the degree to which collocations are encountered in different types of text. It may be that, while collocations are relatively infrequent within a corpus, they may be more frequent within an individual text of a reasonable length or related texts, in the same way that single‐word items are (see, e.g., Hwang & Nation, 1989; Rodgers & Webb, 2011; Schmitt & Carter, 2000; Sutarsyah, Nation, & Kennedy, 1994). However, Boers and Lindstromberg's (2009) analysis of the first 120 pages of a novel indicated that this may not occur to the same degree for collocations.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…It would also be useful to look at the degree to which collocations are encountered in different types of text. It may be that, while collocations are relatively infrequent within a corpus, they may be more frequent within an individual text of a reasonable length or related texts, in the same way that single‐word items are (see, e.g., Hwang & Nation, 1989; Rodgers & Webb, 2011; Schmitt & Carter, 2000; Sutarsyah, Nation, & Kennedy, 1994). However, Boers and Lindstromberg's (2009) analysis of the first 120 pages of a novel indicated that this may not occur to the same degree for collocations.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Much research has been concerned with vocabulary acquisition from reading (and to a lesser extent from listening), but the growing popularity of audiovisual materials calls for more investigations of their affordances for vocabulary acquisition. Some studies have already demonstrated the potential of authentic audiovisual materials for this purpose (e.g., Rodgers & Webb, ; Webb, ), and there are grounds for believing that audiovisual input offers affordances that are absent from audio input alone (Vanderplank, ).…”
mentioning
confidence: 99%
“…They also tend to create affective engagement, encouraging the viewer to watch many related episodes (Vanderplank 2010). Watching successive episodes, in particular, builds on the same background knowledge of the plot and characters, and also entails lower vocabulary load and higher potential for incidental vocabulary learning than watching unrelated programs (Rodgers, Webb 2011). Moreover, the dialogues of TV series tend to resemble spontaneous conversation more than the speech of other audiovisual genres such as documentaries and news broadcasts.…”
Section: Literature Reviewmentioning
confidence: 99%